National Health Systems and COVID-19 Death Toll Doubling Time - Alfaro, Miguel; Muñoz-Godoy, Diego; Vargas, Manuel; Fuertes, Guillermo; Duran, Claudia; Ternero, Rodrigo; Sabattin, Jorge; Gutierrez, Sebastian; Karstegl, Natalia (Frontiers in Public Health, 2021)
COVID-19 has placed stress on all National Health Systems worldwide. Recent studies of the disease have evaluated different variables; quarantine models, mitigation efforts, damage to the mental health, mortality of the population with chronic diseases, diagnosis of the disease, use of masks and social distancing, or mortality regarding different age groups. This study focuses on the four National Health System recognized by the WHO. These systems are: (1) The Beveridge model, (2) the Bismarck model, (3) the National Health insurance model, and (4) the “Out of pocket” model. The study analyzes the response capacity of health systems to the pandemic by comparing the time in days required by the disease to double the number of deaths. The statistical analysis was limited to 56 country representing 70% of the global population. Each country was grouped into the health system defined by WHO. The study compared the medians of time to double the variable number of deaths between health systems using Mood's median test method. The results show a high variability of the temporal trends in each study group; each health system for the three periods analyzed does not maintain stable interquartile ranges. Nevertheless, the results obtained show similar medians between the study groups. The COVID-19 pandemic saturates health systems regardless of their management structures and the result measured with the variable ‘time for doubling of number of deaths’ is similar among the 4 national health systems.